Beyond the ORF: Paralog-specific regulation of RPS7/eS7 mRNAs via 3’-UTRs and promoter sequences - Sachiko Hayashi; Tohru Yoshihisa (PLoS ONE, 2025)
In a classical view, each paralogous ribosomal protein (RP) is equally synthesized and integrated into the ribosome. Therefore, RP-paralog mRNAs are generally believed to be similarly regulated on their transcription and/or stability. In this paper, we report that two Rps7p/eS7 paralogs of Saccharomyces cerevisiae are differently regulated; deletion of RPS7A upregulates RPS7B paralogous mRNA expression but not vice versa. Their 3’-UTR sequences critically regulated the stabilities of both RPS7A and RPS7B mRNAs. Alterations in these sequences led to a diminished expression of RPS7A and RPS7B mRNAs in a transcript-dependent manner, suggesting that RPS7-paralog mRNAs have different properties for their expression and/or stability. The C-terminal tagging of the ORF and mutation analyses in the 3’-UTR indicate that both RPS7-paralog mRNAs critically rely on their 3’-UTRs for mRNA expressions and/or stabilities. We also found that activities of both RPS7A and RPS7B promoters are regulated by abundance of Rps7Ap and that Fhl1p, a key transcriptional regulator of RP genes, is essential for transcription of RPS7B but not RPS7A while simultaneous deletion of a consensus sequence for Fhl1p in the RPS7A promoter region and the FHL1 gene completely abolishes the promoter activity. These results indicate that yeast has a distinct buffering system for Rps7p production between the two RPS7-paralogs, which is sensitive to variation on their 3’-UTRs and is partially mediated in a transcription-dependent manner.